MOTIVASI BELAJAR PADA PESERTA DIDIK KELAS X SMKN 1 PONTIANAK TAHUN AJARAN 2017/2018 - Labret, Anassia; Wicaksono, Luhur; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractMotivation to learn is a series of business or impulse that causes someone to want and want to do something in achieving the desired objectives.The learning process that involves various components should be packaged in a systematic study. So that produce optimal learning results. The success of the learning process where the parameter is the result of learning, it is spurring both teachers and students to strive to achieve that goal. Therefore, researchers wanted to know the motivation to learn on  Students of Class X SMK Negeri 1 Pontianak in Academic Year 2017/2018. A common problem in this research is"How the motivation of learners in class X School SMK Negeri 1 Pontianak academic year 2017/2018". This study aims to identify and describe the motivation of learners in class X School SMK Negeri 1 Pontianak 2017/2018 school year. The method used in this research is descriptive method of analysis of research form. The population in this study were 73 learners in class X OTP 1 which, amounting to 37 people and a class X OTP 2 totaling 36 people. This study uses a quantitative approach. Data collection techniques in this research is the technique of direct and indirect communication with a data collector in the form of a questionnaire. Data were analyzed using percentages. Based on the analysis of the motivation of learners class X SMK Negeri 1 Pontianak 2017/2018 school year as a whole reached 82.54% with the category of "Very Good".        Keywords: motivation to learn, the learners